IDENTIFIKASI JAMUR PATOGEN TANAMAN TOMAT (Lycopersicum esculentum Mill.) DI LAHAN KERING AMOR-AMOR LOMBOK UTARA - nindi faridatul hasanah*1; Irwan Muthahanas*2; Mulat Isnain*3 (CROP AGRO, Scientific Journal of Agronomy, 2019)
ABSTRACT The aim of this research is to determine the pathogenic fungi that infect tomatoes in farmer's land and level of damage in Amor-Amor. This research was conducted from October 2017 to January 2018 which was carried out in Amor-Amor Village, North Lombok Regency and in the Microbiology Laboratory, Faculty of Agriculture, University of Mataram.The method used in this research was descriptive by collecting data in the field directly. The results showed that with highest intensity of disease is caused by the fungus Alternaria sp. that is 48% in tymoti varieties and 62.50% in servo varieties and followed by Phytophthora sp. with disease incidents of 5.33% in tymoti varieties, 14.66% in servo varieties, and Rhizoctonia sp. 28.83% in tymoti varieties, 13.33% in servo varieties respectively.